2020
DOI: 10.1111/anhu.12298
|View full text |Cite
|
Sign up to set email alerts
|

Caring for “Hassle‐Free Highs” in Amsterdam

Abstract: In this article we present some of our ethnographic findings from the city of Amsterdam, where health authorities and practitioners have implemented harm reduction strategies that build on and reinforce young drug users' practices of selfregulation and care. Amsterdam's harm reduction policies build on the premises that harm is not a direct, always present consequence of recreational drug use and that harm reduction strategies will be more effective when they engage with the collective, material, and affective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The key informants recruited for this study were selected purposively as informants act as a rich source of information central to research themes [39] and allow diversity of data [40]. They were selected because they work in or are in close contact with the rabies surveillance system, i.e., are knowledgeable of the system and how it works.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…The key informants recruited for this study were selected purposively as informants act as a rich source of information central to research themes [39] and allow diversity of data [40]. They were selected because they work in or are in close contact with the rabies surveillance system, i.e., are knowledgeable of the system and how it works.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Over half got information from internet websites and online discussion forums, books and peer-reviewed articles, and friends. Studies have shown that effective harm reduction occurs at the grassroots level (Hardon et al, 2020), based at least in part on community-and peer-based and sometimes online (Barratt, Allen, & Lenton, 2014) groups who generate norms and practices supporting self-regulation, prevention, and intervention in case of harm. This is in contrast with topdown medical information, as well as prohibition-oriented regulatory frameworks that increase the risk of harmful use (Harder, Steinmetz, & Kohek, 2023).…”
Section: Significance and Implications Medicalization And Social Effi...mentioning
confidence: 99%